2002
DOI: 10.1124/jpet.301.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glutathione-Dependent Thiopurine Prodrugs: Evidence for Enhanced Cytotoxicity in Tumor Cells and for Decreased Bone Marrow Toxicity in Mice

Abstract: Elevated glutathione (GSH) levels have been detected in many tumors compared with the healthy, surrounding tissue. Often, this GSH up-regulation is associated with drug resistance. The prodrugs 6-(2-acetylvinylthio)guanine (AVTG) and 6-(2-acetylvinylthio)purine (AVTP) contain a novel butenone moiety that allows the prodrugs to react selectively with sulfhydryl nucleophiles to release the chemotherapeutic drug 6-thioguanine (6-TG) or 6-mercaptopurine (6-MP), respectively. The cellular uptake and metabolism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…These results support our previous findings in which cis-AVTP and trans-AVTG exhibited similar cytotoxicities that were greater than or comparable to those of 6-MP and 6-TG, respectively (Gunnarsdottir et al, 2002a).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These results support our previous findings in which cis-AVTP and trans-AVTG exhibited similar cytotoxicities that were greater than or comparable to those of 6-MP and 6-TG, respectively (Gunnarsdottir et al, 2002a).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, treatment with cis-AVTP, trans-AVTG, and 6-TG yielded distinct patterns of metabolite composition and quanti-ties in mouse tissues, suggesting differences in tissue distribution and metabolism among the compounds (Gunnarsdottir and Elfarra, 2003). Also, when the in vitro cytotoxicities of cis-AVTP and trans-AVTG were assessed in the renal cell carcinoma cell lines ACHN and A-498, the prodrugs exhibited similar cytotoxicities that were greater than the cytotoxicity of 6-MP but comparable with that of 6-TG after a 72-h drug incubation (Gunnarsdottir et al, 2002a). Likewise, studies comparing the cytotoxicities of cis-AVTP and 6-MP after different incubation times revealed that even after as little as 24 h of drug incubation, extensive cytotoxicity was detected in incubation with cis-AVTP, whereas no cytotoxicity was observed in 6-MP incubations (Gunnarsdottir et al, 2002a).…”
mentioning
confidence: 87%
See 3 more Smart Citations